PENGARUH PERKEMBANGAN TEKNOLOGI DI ERA GLOBALISASI DAN PERAN PENDIDIKAN TERHADAP DEGRADASI MORAL PADA REMAJA - Tranggono, Tranggono; Jasmin, Kamila Jastisia; Amali, Muhammad Rizqi; Aginza, Lola Nashwa; Sulaiman, Shania Zahra Rizqitta; Ferdhina, Femas Agil; Effendie, Daafa Abdan Maulaana (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Technological developments in the era of globalization can have a negative impact on its users. Technology makes it easy to access information and content that is not in accordance with social norms in society. Adolescents who are not fully able to filter the information available can lead to increased moral degradation. Moral degradation is referred to as a decline in moral quality that is not in accordance with the nation's identity so that it can damage the image of the nation. Adolescents who are exposed to the negative effects of technology over a long period of time can affect their perception of morals and values in society. Excessive use of technology can also reduce adolescent social involvement in interacting directly which can affect sympathy and empathy to their environment. Moral degradation in adolescents is a challenge for educators to strengthen character education as an effort to prevent declining moral quality. With the formation of good morals, the next generation of a superior and dignified nation will be created. The results of this study show that technology in the era of globalization affects moral degradation in adolescents and character education as an effort to prevent it. This research is a qualitative descriptive research with a correlational method, which is a method to determine the influence between one variable and another variable and see the degree of relationship that exists between variables